Proliferative activity of epidermocytes in healing of chemical burns of IIIa stage during experiment - Zagorulko, A.K.; Golubinskaya, E.P.; Filonenko, T.G.; Davydova, A.A.; Birkun, A.A.; Nesterov, E.N.; Ozerova, N.Yu.; Savina, T.V. (Pathologia, 2013)
Activation of the proliferative activity of the epidermis in the group treated with BAPC is observed on the third day of the experiment, which indicates the beginning of the regeneration of the epidermis. By the tenth day of the experiment in group with burns treated with BAPC against the background of full epidermization of burn surface the indicators of proliferative activity of basal cells almost coincide with the indicators of control group, confirming the completion of repair processes on 3 - 4 days earlier than in case of treatment with the recommended drug «Levomekol» .